Testing the "Test and Treat" HIV prevention strategy: the example of Côte d'Ivoire - (:unkn) unknown (My University, 2013)
Increasing evidence suggests that early antiretroviral treatment (ART) of HIV-infected people is beneficial at individual level and may also present benefits at population level. Thus, the potential of the Test and Treat strategy to curtail the HIV epidemic seems promising, especially in the context of sub-Saharan Africa. This strategy relies on universal HIV testing combined with immediate initiation of ART among those diagnosed HIV-positive and raises many issues, especially regarding socio-behavioural aspects. Relying on two studies conducted in Côte d'Ivoire, the objective of this thesis was to understand some of the socio-behavioural issues of expanding HIV testing and treatment. Based on an intervention trial, we studied the impact of an early ART initiation on sexual behaviours and on HIV transmission risk among adults engaged in various types of partnerships. Besides, the analysis of a nationally-representative survey identified the main socio-behavioural and contextual barriers to uptake of HIV testing among the general population of Côte d'Ivoire. The results of this thesis highlight important preventive benefits, behavioural and biological, resulting from early entry into care and early initiation of ART. Analyses conducted on the uptake of HIV testing in the general population underlined the efforts still needed to allow the maximal public health impact of early ART. Overall, this work provides some insights on the conditions of success and the real world efficacy of the Test and Treat strategy in the context of West Africa.
Keywords: African Research